Masjid Agung Sumenep: Akar Historis Toleransi Masyarakat Ujung Timur Pulau Garam: Sumenep Grand Mosque: Historical Roots of Tolerance of the East End of Salt Island - Andika, Fajri (Nur Science Institute, 2022)
This paper discusses the history of the construction of the Sumenep Great Mosque and the symbolization of Islamic art in the architecture of the mosque which was built in the 18th century. Methodologically, the type of research used in this study is descriptive qualitative, with data collection techniques of library research, observation, interviews, and documentation. The results of the study show that the Sumenep Grand Mosque was built during the Panembahan Sumolo era (1763 AD). The architectural design of this mosque is influenced by various cultures: Chinese, Arab-Persian, Javanese, and European, which is a symbol of tolerance and peace for the people of the eastern tip of Salt Island